A carbonized gelling material and its preparation method and application

The preparation of lignin-based carbon fibers through homogenization of calcium raw materials and siliceous raw materials and electrospinning. Combined with high temperature treatment, the problem of insufficient performance of carbonized gelling materials is solved, and carbonization is achieved with high interface bonding strength and good comprehensive performance. Preparation of gelling materials reduces costs.

CN116217103BActive Publication Date: 2025-01-14山东京韵泰博负碳科技有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310146850.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-20
Publication Date
2025-01-14
Estimated Expiration
2043-02-20

AI Technical Summary

Technical Problem

The existing carbonized gelling materials lack performance in tensile strength and toughness, making it difficult to significantly improve the overall performance.

Method used

After homogenizing calcium raw materials and silicon raw materials, lignin-based carbon fiber raw materials are prepared by electrospinning, and mixed with calcium and silicon mixture for pretreatment and high temperature treatment to form a carbonized gelling material with high interface bonding strength. .

Benefits of technology

It significantly improves the interface bonding strength and comprehensive performance of carbonized gelled materials, improves the density and mechanical properties of the materials, and reduces the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116217103B_ABST
    Figure CN116217103B_ABST
Patent Text Reader

Abstract

The present invention provides a carbonized gelling material and a preparation method and application thereof; the preparation method comprises the following steps: a) homogenizing a calcium raw material and a silicon raw material to obtain a calcium-silicon mixture; electrospinning lignin to obtain lignin-based carbon fiber precursor; b) mixing the calcium-silicon mixture and the lignin-based carbon fiber precursor, and then pre-treating and high-temperature treating them in sequence, and cooling them to obtain a carbonized gelling material. Compared with the prior art, the preparation method provided by the present invention adopts specific raw materials and specific process steps to achieve better overall interaction, and the prepared carbonized gelling material has high interface bonding strength and better comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbonized gelling materials, and more specifically to a carbonized gelling material and a preparation method and application thereof. Background Art

[0002] The silicate minerals in traditional cement can all undergo carbonization reaction. The cementitious materials can absorb a certain amount of CO2 during the carbonization and hardening process, permanently fixing CO2 and producing a certain strength. With the advancement of industrial level, industrial waste has increased dramatically. Using carbon-absorbing cementitious materials to prepare new carbonized cementitious materials is one of the future development directions.

[0003] Carbon fiber is widely used in automobile transportation, engineering construction and other aspects due to its high tensile strength, low density and good durability. With the depletion of petroleum resources, it is particularly important to reduce the preparation cost of carbon fiber, and the key factor that determines the performance and cost of carbon fiber is the carbon fiber precursor itself. As papermaking black liquor, how to make use of lignin as a resource has always been a headache for people, but as the most abundant biomass material in nature, it has low cost, wide sources and high fixed carbon content, which has attracted the interest of many scholars. The Chinese patent with publication number CN112760751A discloses a method for preparing self-activated lignin-based micro-nano activated carbon fiber with controllable pore size, extracting acid lignin from biomass raw materials by acid extraction, spinning acidified lignin into carbon fiber precursor by electrostatic spinning technology, and then performing subsequent steps. The Chinese patent with publication number CN111393050A discloses a method for preparing γ-C2S-based cementitious material, using industrial raw materials to prepare γ-C2S, which reduces the production cost to a certain extent, but reduces the compressive strength of the cementitious material, and the carbonization performance needs to be improved. The Chinese patent with publication number CN111393051A discloses a grinding-free carbonization hardening cement clinker and its preparation method, which mainly controls the content of free calcium oxide in the clinker to make the clinker self-pulverizing and achieve the effect of grinding-free. Carbon-absorbing cementitious materials have been vigorously developed in many countries as a new type of green building material. They can be widely used in industrial production such as artificial stone and prefabricated products, which is of great significance to achieving the goal of "carbon neutrality".

[0004] However, the current carbonized cementitious materials cannot significantly improve the comprehensive performance of carbonized cementitious materials only through the research and design of cementitious materials, so that there is still a lot of room for improvement in the tensile strength and toughness of carbonized cementitious materials. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a carbonized cementitious material and a preparation method and application thereof. The carbonized cementitious material prepared by the preparation method provided by the present invention has high interface bonding strength and good comprehensive performance.

[0006] The present invention provides a method for preparing a carbonized gelled material, comprising the following steps:

[0007] a) homogenizing a calcium raw material and a silicon raw material to obtain a calcium-silicon mixture; and preparing lignin-based carbon fiber precursor by electrostatic spinning of lignin;

[0008] b) The calcium-silicon mixture and the lignin-based carbon fiber precursor are mixed, pretreated and treated at high temperature in sequence, and then cooled to obtain a carbonized gelled material.

[0009] Preferably, the calcium raw material in step a) is selected from one or more of limestone, shell and steel slag;

[0010] The siliceous raw material is selected from one or more of sandstone, coal slag and fly ash;

[0011] The usage ratio of the calcium raw material to the silicon raw material is the molar ratio of calcium oxide in the calcium raw material to silicon dioxide in the silicon raw material (2-3):1.

[0012] Preferably, the homogenization treatment in step a) is carried out in one or more of a mixer and a ball mill.

[0013] Preferably, the lignin in step a) is selected from one or more of alkali lignin, organic solvent lignin and enzymatic lignin;

[0014] The fiber diameter of the lignin-based carbon fiber precursor is 100nm-200nm, and the aspect ratio is 100-200.

[0015] Preferably, the electrospinning preparation method of the lignin-based carbon fiber precursor is to uniformly mix lignin and polyacrylonitrile in a ratio of 1 to 7:99 to 93 to form a mixture A, and prepare a lignin-based carbon fiber spinning solution by mixing the mixture A with a solvent in a mass concentration ratio of 8 to 13:100, wherein the solvent includes but is not limited to one or more of dimethyl sulfoxide, NN dimethylformamide or NN dimethylacetamide; and then prepare the lignin-based carbon fiber precursor by electrospinning; wherein the parameters during the electrospinning process are: high-voltage electric field positive electrode voltage +10 to 20 kV, negative electrode -2 to 5 kV, injection liquid flow rate 0.1 to 1.5 mL / h, the distance between the needle and the roller surface is 10 to 15 cm; the ambient temperature is 20 to 45 ° C, and the humidity is 35 to 50%

[0016] Preferably, the mass ratio of the calcium-silicon mixture to the lignin-based carbon fiber precursor in step b) is (0.01-0.1):1.

[0017] Preferably, the pretreatment in step b) is preheating; the preheating temperature is 150°C to 400°C, and the time is 2h to 6h; the high temperature treatment process is carried out under the protection of inert gas; the heating rate of the high temperature treatment is 5°C / min to 15°C / min, the temperature is 1050°C to 1650°C, and the insulation time is 3h to 9h.

[0018] The present invention also provides a carbonized gelling material, which is prepared by the preparation method described in the above technical solution.

[0019] The present invention also provides a carbonized gelling material product, which is prepared by carbonizing and curing the carbonized gelling material; the carbonized gelling material is the carbonized gelling material described in the above technical solution.

[0020] Preferably, the carbonization curing time is 48 h to 86 h, the concentration is 10% to 100%, and the pressure is 0.1 MPa to 0.6 MPa.

[0021] The present invention provides a carbonized gelling material and a preparation method and application thereof; the preparation method comprises the following steps: a) homogenizing a calcium raw material and a silicon raw material to obtain a calcium-silicon mixture; electrospinning lignin to obtain lignin-based carbon fiber precursor; b) mixing the calcium-silicon mixture and the lignin-based carbon fiber precursor, and then pre-treating and high-temperature treating them in sequence, and cooling them to obtain a carbonized gelling material. Compared with the prior art, the preparation method provided by the present invention adopts specific raw materials and specific process steps to achieve better overall interaction, and the prepared carbonized gelling material has high interface bonding strength and better comprehensive performance.

[0022] At the same time, the preparation method provided by the present invention has simple process, easily controllable conditions, low cost and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention provides a process flow chart of the method for preparing the carbonized gelled material. DETAILED DESCRIPTION

[0024] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The present invention provides a method for preparing a carbonized gelled material, comprising the following steps:

[0026] a) homogenizing a calcium raw material and a silicon raw material to obtain a calcium-silicon mixture; and preparing lignin-based carbon fiber precursor by electrostatic spinning of lignin;

[0027] b) The calcium-silicon mixture and the lignin-based carbon fiber precursor are mixed, pretreated and treated at high temperature in sequence, and then cooled to obtain a carbonized gelled material.

[0028] The present invention firstly homogenizes a calcium raw material and a silicon raw material to obtain a calcium-silicon mixture; and obtains a lignin-based carbon fiber precursor by electrostatic spinning of lignin.

[0029] In the present invention, the calcium raw material is preferably selected from one or more of limestone, shell and steel slag, more preferably limestone, shell or steel slag. In the present invention, the mass content of calcium oxide in the calcium raw material is preferably ≥45%. The present invention has no particular restriction on the source of the calcium raw material, and commercial products well known to those skilled in the art can be used.

[0030] In the present invention, the siliceous raw material is preferably selected from one or more of sandstone, coal slag and fly ash, and more preferably sandstone, coal slag or fly ash. In the present invention, the mass content of calcium oxide in the siliceous raw material is preferably ≥80%. The present invention has no special restrictions on the source of the siliceous raw material, and commercial products well known to those skilled in the art can be used.

[0031] In the present invention, the usage ratio of the calcareous raw material to the siliceous raw material is preferably a molar ratio of calcium oxide in the calcareous raw material to silicon dioxide in the siliceous raw material (2-3):1; the ingredients can be mixed after conversion.

[0032] In the present invention, the homogenization treatment is preferably carried out in one or more of a mixer and a ball mill.

[0033] In the present invention, the lignin is preferably selected from one or more of alkali lignin, organic solvent lignin and enzymatic lignin, and is more preferably alkali lignin. In a preferred embodiment of the present invention, the lignin is alkali lignin with a lignin purity of ≥70%. The present invention has no special restrictions on the source of the lignin, and commercial products known to those skilled in the art can be used.

[0034] In the present invention, the electrospinning preparation method of the lignin-based carbon fiber precursor is as follows: lignin and polyacrylonitrile are uniformly mixed in a ratio of 1 to 7:99 to 93 to form a mixture A, and the mixture A and the solvent are mixed in a mass concentration ratio of 8 to 13:100 to prepare a lignin-based carbon fiber spinning solution, wherein the solvent includes but is not limited to one or more of dimethyl sulfoxide, NN dimethylformamide or NN dimethylacetamide; and then the lignin-based carbon fiber precursor is prepared by electrospinning; wherein the parameters in the electrospinning process are: the positive electrode voltage of the high-voltage electric field is +10 to 20 kV, the negative electrode is -2 to 5 kV, the injection liquid flow rate is 0.1 to 1.5 mL / h, and the distance between the needle and the roller surface is 10 to 15 cm; the ambient temperature is 20 to 45 ° C, and the humidity is 35 to 50%.

[0035] In the present invention, the fiber diameter of the lignin-based carbon fiber precursor is preferably 100 nm to 200 nm, and the aspect ratio is preferably 100 to 200.

[0036] Afterwards, the present invention mixes the calcium-silicon mixture and the lignin-based carbon fiber precursor, performs pretreatment and high-temperature treatment in sequence, and obtains a carbonized gelled material after cooling.

[0037] In the present invention, the mass ratio of the calcium-silicon mixture to the lignin-based carbon fiber precursor is preferably (0.01-0.1):1.

[0038] In the present invention, the pretreatment method is preferably preheating, using a preheating device well known to those skilled in the art; the preheating temperature is preferably 150°C to 400°C, more preferably 180°C to 350°C, and the preheating time is preferably 2h to 6h, more preferably 3h.

[0039] In the present invention, the high temperature treatment process is preferably carried out under the protection of an inert gas, and the inert gas is preferably one or more of helium, nitrogen, and argon gases well known to those skilled in the art, more preferably nitrogen or argon.

[0040] In the present invention, the heating rate of the high temperature treatment is preferably 5°C / min to 15°C / min, more preferably 10°C / min, the temperature is preferably 1050°C to 1650°C, more preferably 1100°C to 1600°C, and the holding time is preferably 3h to 9h, more preferably 4h to 8h.

[0041] In the present invention, the cooling process preferably reduces the temperature of the high temperature treatment to room temperature at a cooling rate of 5°C / min to 15°C / min (more preferably 10°C / min).

[0042] The preparation method provided by the present invention adopts specific raw materials in combination with specific process steps to achieve better overall interaction, and the prepared carbonized cementitious material has high interface bonding strength and good comprehensive performance; at the same time, the preparation method provided by the present invention has simple process, easy-to-control conditions, low cost, and broad application prospects.

[0043] The present invention also provides a carbonized gelling material, which is prepared by the preparation method described in the above technical solution. The present invention provides a carbonized gelling material containing lignin-based carbon fibers, in which lignin-based carbon fibers are grown in situ; the present invention simultaneously calcines the carbonized gelling material and the lignin-based carbon fiber precursor at high temperature, and the carbonized gelling material in the prepared carbonized gelling material containing lignin-based carbon fibers and the lignin-based carbon fibers work together to change the internal structure of the carbonized gelling material, effectively limit the occurrence and development of original cracks formed by early segregation and shrinkage of the carbonized gelling material, reduce the cracks generated in the preparation process of the carbonized gelling material, and the lignin-based carbon fibers fill the pores of the carbonized gelling material, making its structure more compact, and effectively improving the comprehensive performance of the carbonized gelling material.

[0044] The present invention also provides a carbonized gelling material product, which is prepared by carbonizing and curing the carbonized gelling material; the carbonized gelling material is the carbonized gelling material described in the above technical solution.

[0045] In view of the problems of low interfacial bonding strength, low tensile strength and insufficient toughness existing in existing carbonized cementitious materials, the present invention provides a new type of carbonized cementitious material that can effectively enhance the interfacial bonding strength of carbonized cementitious materials, namely, a carbonized cementitious material containing lignin-based carbon fibers, specifically a carbonized cementitious material with lignin-based carbon fibers grown in situ on the surface.

[0046] In the present invention, the carbonization curing time is preferably 48 h to 86 h, more preferably 72 h, the concentration is preferably 10% to 100%, and the pressure is preferably 0.1 MPa to 0.6 MPa.

[0047] Principle of the present invention:

[0048] The present invention in situ grows lignin-based carbon fibers on a carbonized gelling material to increase the interfacial contact area of ​​the carbonized gelling material, thereby strengthening the interfacial bonding effect between the carbonized gelling materials. A carbonized gelling material containing lignin-based carbon fibers is prepared in situ, and the dispersion uniformity of the material itself is ensured by means of the steric hindrance effect of the lignin-based carbon fibers themselves. The voids in the carbonized gelling material are filled by using the characteristics of the lignin-based carbon fibers themselves, thereby further promoting the mechanical properties of the carbonized gelling material. At the same time, the carbon fibers utilize their own properties to enhance the comprehensive properties of the carbonized gelling material.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] (1) The present invention grows lignin-based carbon fibers in situ on the carbonized gel surface, which can significantly improve the bonding strength between the lignin-based carbon fibers and the carbonized gel matrix and improve the interface transition zone;

[0051] (2) The present invention utilizes the steric hindrance effect of the lignin-based carbon fiber itself to improve its dispersibility during the preparation and use process, give full play to the role of the lignin-based carbon fiber and the carbonized cementitious material and fill the original gaps in the carbonized cementitious material, so that the carbonized cementitious material is tightly combined inside. The two work together to further improve the density of the carbonized cementitious material and effectively improve the comprehensive performance of the carbonized cementitious material. At the same time, the carbon fiber utilizes its own performance to enhance the comprehensive performance of the carbonized cementitious material.

[0052] The present invention provides a carbonized gelling material and a preparation method and application thereof; the preparation method comprises the following steps: a) homogenizing a calcium raw material and a silicon raw material to obtain a calcium-silicon mixture; electrospinning lignin to obtain lignin-based carbon fiber precursor; b) mixing the calcium-silicon mixture and the lignin-based carbon fiber precursor, and then pre-treating and high-temperature treating them in sequence, and cooling them to obtain a carbonized gelling material. Compared with the prior art, the preparation method provided by the present invention adopts specific raw materials and specific process steps to achieve better overall interaction, and the prepared carbonized gelling material has high interface bonding strength and better comprehensive performance.

[0053] At the same time, the preparation method provided by the present invention has simple process, easily controllable conditions, low cost and broad application prospects.

[0054] In order to further illustrate the present invention, the following examples are provided for detailed description. The raw materials used in the following examples and comparative examples of the present invention are all commercially available.

[0055] The flexural test method is: after the flexural test sample reaches the curing test time (28 days), test one group of the three groups of samples at the curing age to ensure the accuracy of the data. Before the test, ensure that there is no obvious moisture on the surface of the sample, and the cleaned sample should be fully wrapped with a wet and clean cloth to prevent the sample from drying. After that, the mechanical properties of the mechanical test sample are tested, and the analysis instrument uses a compression and flexural integrated machine.

[0056] Example 1

[0057] According to a calcium-silicon molar ratio of 2.0, steel slag with a calcium oxide content of 45% and fly ash with a silicon dioxide content of 80% are homogenized by a ball mill to obtain a calcium-silicon mixture; alkali lignin with a lignin purity of 70% is prepared by electrostatic spinning to obtain lignin-based carbon fiber precursors with a diameter of 100nm-200nm and an aspect ratio of 150, wherein the lignin-based carbon fiber precursor is prepared by an electrostatic spinning method, specifically, lignin and polyacrylonitrile are mixed uniformly in a ratio of 5:95 to form a mixture A, the mixture A is mixed with a solvent in a mass concentration ratio of 8:100 to obtain a lignin-based carbon fiber spinning solution, the solvent is dimethyl sulfoxide, and then electrostatic spinning is performed. The lignin-based carbon fiber precursor was prepared by the electrospinning method, wherein the parameters in the electrospinning process were: high-voltage electric field positive electrode voltage +13kV, negative electrode -2kV, injection liquid flow rate 0.1mL / h, and the distance between the needle and the roller surface was 10cm; the ambient temperature was 25℃, and the humidity was 30%; the two were mixed, wherein the mass ratio of the lignin-based carbon fiber precursor and the calcium silicon mixture was 0.01:1, and then placed in a preheating device with the temperature set to 180℃ and the insulation time being 3h for pretreatment, and then under nitrogen gas conditions, the temperature was raised to 1100℃ at a heating rate of 10℃ / min, and the temperature was maintained for 4h, and then cooled to room temperature at a cooling rate of 10℃ / min to obtain a new carbonized cementitious material.

[0058] The new carbonized cementitious material of this embodiment was subjected to carbonization curing for 72 hours at a concentration of 10% and a pressure of 0.1 MPa to obtain a new carbonized cementitious product. The mechanical properties of the new carbonized cementitious product were tested in accordance with GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", and the carbonization degree of the product was evaluated by the loss on ignition calcium carbonate method.

[0059] The test shows that the novel carbonized gelled material of this embodiment has a small amount of fine particles, and the compressive strength of the carbonized product of the novel carbonized gelled material (after carbonization for 24 hours) is 67.8 MPa, and the degree of carbonization is 36.6%.

[0060] Example 2

[0061] According to the calcium-silicon molar ratio of 3.0, limestone with a calcium oxide content of 65% and coal slag with a silicon dioxide content of 90% are homogenized by a ball mill to obtain a calcium-silicon mixture; alkali lignin with a lignin purity of 90% is prepared by electrostatic spinning to obtain lignin-based carbon fiber precursors with a diameter of 100nm-200nm and an aspect ratio of 150, wherein the lignin-based carbon fiber precursor is prepared by the electrostatic spinning method, specifically: lignin and polyacrylonitrile are uniformly mixed in a ratio of 6:94 to form a mixture A, the mixture A is mixed with a solvent in a mass concentration ratio of 9:100 to obtain a lignin-based carbon fiber spinning solution, the solvent is dimethyl sulfoxide, and then electrostatic spinning is performed Lignin-based carbon fiber precursor was prepared by the method, wherein the parameters in the electrospinning process were: high-voltage electric field positive electrode voltage +16kV, negative electrode -4kV, injection liquid flow rate 0.5mL / h, needle distance from the roller surface 15cm; ambient temperature 28℃, humidity 35%; the two were mixed, wherein the mass ratio of lignin-based carbon fiber precursor to calcium silicon mixture was 0.1:1, then placed in a preheating device with the temperature set to 350℃, and the insulation time was 3h for pretreatment, and then under argon gas conditions, the temperature was raised to 1600℃ at a heating rate of 10℃ / min, maintained for 4h, and then cooled to room temperature at a cooling rate of 10℃ / min to obtain a new carbonized gelled material.

[0062] The new carbonized cementitious material of this embodiment was subjected to carbonization curing for 72 hours at a concentration of 10% and a pressure of 0.1 MPa to obtain a new carbonized cementitious product. The mechanical properties of the new carbonized cementitious product were tested in accordance with GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", and the carbonization degree of the product was evaluated by the loss on ignition calcium carbonate method.

[0063] The test shows that the novel carbonized gelling material of this embodiment has a small amount of fine particles, and the compressive strength of the carbonized product of the novel carbonized gelling material (after carbonization for 24 hours) is 79.3 MPa, and the degree of carbonization is 42.4%.

[0064] Example 3

[0065] According to the calcium-silicon molar ratio of 2.0, shells with a calcium oxide content of 65% and sandstone with a silicon dioxide content of 90% are homogenized by a ball mill to obtain a calcium-silicon mixture; alkali lignin with a lignin purity of 90% is prepared by electrostatic spinning to obtain lignin-based carbon fiber precursors with a diameter of 100nm-200nm and an aspect ratio of 150, wherein the lignin-based carbon fiber precursor is prepared by the electrostatic spinning method, specifically: lignin and polyacrylonitrile are mixed uniformly in a ratio of 7:93 to form a mixture A, the mixture A is mixed with a solvent in a mass concentration ratio of 10:100 to obtain a lignin-based carbon fiber spinning solution, the solvent is dimethyl sulfoxide, and then electrostatic spinning is performed Lignin-based carbon fiber precursor was prepared by the method, wherein the parameters in the electrospinning process were: high-voltage electric field positive electrode voltage +16kV, negative electrode -5kV, injection liquid flow rate 0.5mL / h, needle tip distance from roller surface 15cm; ambient temperature 28℃, humidity 40%; the two were mixed, wherein the amount of lignin-based carbon fiber precursor and calcium silicon mixture was 0.05:1 by mass ratio, then placed in a preheating device with the temperature set to 180℃, and the insulation time was 3h for pretreatment, and then under nitrogen gas conditions, the temperature was raised to 1100℃ at a heating rate of 10℃ / min, maintained for 4h, and then cooled to room temperature at a cooling rate of 10℃ / min to obtain a new carbonized cementitious material.

[0066] The new carbonized cementitious material of this embodiment was subjected to carbonization curing for 72 hours at a concentration of 10% and a pressure of 0.1 MPa to obtain a new carbonized cementitious product. The mechanical properties of the new carbonized cementitious product were tested in accordance with GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", and the carbonization degree of the product was evaluated by the loss on ignition calcium carbonate method.

[0067] The test shows that the novel carbonized gelling material of this embodiment has a small amount of fine particles, and the compressive strength of the carbonized product of the novel carbonized gelling material (after carbonization for 24 hours) is 70.6 MPa, and the degree of carbonization is 39.1%.

[0068] Example 4

[0069] According to the calcium-silicon molar ratio of 3.0, limestone with a calcium oxide content of 45% and fly ash with a silicon dioxide content of 80% are homogenized by a ball mill to obtain a calcium-silicon mixture; alkali lignin with a lignin purity of 70% is prepared by electrostatic spinning to obtain lignin-based carbon fiber precursors with a diameter of 100nm-200nm and an aspect ratio of 150, wherein the lignin-based carbon fiber precursor is prepared by the electrostatic spinning method, specifically: lignin and polyacrylonitrile are mixed uniformly in a ratio of 6:94 to form a mixture A, the mixture A and a solvent are mixed in a mass concentration ratio of 9:100 to obtain a lignin-based carbon fiber spinning solution, the solvent is dimethyl sulfoxide, and then electrostatic spinning is performed Lignin-based carbon fiber precursor was prepared by the method, wherein the parameters in the electrospinning process were: high-voltage electric field positive electrode voltage +17kV, negative electrode -4kV, injection liquid flow rate 0.8mL / h, needle tip distance from roller surface 15cm; ambient temperature 28℃, humidity 35%; the two were mixed, wherein the amount of lignin-based carbon fiber precursor and calcium silicon mixture was 0.075:1 by mass ratio, then placed in a preheating device with the temperature set to 350℃, and the insulation time was 3h for pretreatment, and then under argon gas conditions, the temperature was raised to 1600℃ at a heating rate of 10℃ / min, maintained for 4h, and then cooled to room temperature at a cooling rate of 10℃ / min to obtain a new carbonized gelled material.

[0070] The new carbonized cementitious material of this embodiment was subjected to carbonization curing for 72 hours at a concentration of 10% and a pressure of 0.1 MPa to obtain a new carbonized cementitious product. The mechanical properties of the new carbonized cementitious product were tested in accordance with GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", and the carbonization degree of the product was evaluated by the loss on ignition calcium carbonate method.

[0071] The test shows that the novel carbonized gelling material of this embodiment has a small amount of fine particles, and the compressive strength of the carbonized product of the novel carbonized gelling material (after carbonization for 24 hours) is 76.4 MPa, and the degree of carbonization is 41.3%.

[0072] Example 5

[0073] According to the calcium-silicon molar ratio of 2.5, limestone with a calcium oxide content of 55% and fly ash with a silicon dioxide content of 85% are homogenized by a ball mill to obtain a calcium-silicon mixture; alkali lignin with a lignin purity of 80% is prepared by electrostatic spinning to obtain lignin-based carbon fiber precursors with a diameter of 100nm-200nm and an aspect ratio of 150, wherein the lignin-based carbon fiber precursor is prepared by the electrostatic spinning method, specifically: lignin and polyacrylonitrile are mixed uniformly in a ratio of 7:93 to form a mixture A, the mixture A is mixed with a solvent in a mass concentration ratio of 9:100 to obtain a lignin-based carbon fiber spinning solution, the solvent is dimethyl sulfoxide, and then electrostatic spinning is performed Lignin-based carbon fiber precursor was prepared by the method, wherein the parameters in the electrospinning process were: high-voltage electric field positive electrode voltage +17kV, negative electrode -3kV, injection liquid flow rate 1.0mL / h, needle tip distance from roller surface 15cm; ambient temperature 28℃, humidity 40%; the two were mixed, wherein the amount of lignin-based carbon fiber precursor and calcium silicon mixture was 0.1:1 by mass ratio, then placed in a preheating device with the temperature set to 350℃, and the insulation time was 3h for pretreatment, and then under nitrogen gas conditions, the temperature was raised to 1600℃ at a heating rate of 10℃ / min, maintained for 8h, and then cooled to room temperature at a cooling rate of 10℃ / min to obtain a new carbonized cementitious material.

[0074] The new carbonized cementitious material of this embodiment was subjected to carbonization curing for 72 hours at a concentration of 10% and a pressure of 0.1 MPa to obtain a new carbonized cementitious product. The mechanical properties of the new carbonized cementitious product were tested in accordance with GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", and the carbonization degree of the product was evaluated by the loss on ignition calcium carbonate method.

[0075] The test shows that the novel carbonized gelled material of this embodiment has a small amount of fine particles, and the compressive strength of the carbonized product of the novel carbonized gelled material (after carbonization for 24 hours) is 82.2 MPa, and the degree of carbonization is 42.7%.

[0076] Comparative Example 1

[0077] According to the calcium-silicon molar ratio of 2.0, limestone with a calcium oxide content of 45% and fly ash with a silicon dioxide content of 80% are homogenized by a ball mill to obtain a calcium-silicon mixture; then, the mixture is placed in a preheating device with the temperature set to 200°C and the insulation time is 3 hours for pretreatment, and then the temperature is increased to 1200°C at a heating rate of 10°C / min, and the mixture is kept at this temperature for 4 hours, and then the mixture is cooled to room temperature at a cooling rate of 10°C / min to obtain a carbonized cementitious material.

[0078] The carbonized cementitious material of this comparative example was subjected to carbonization curing for 72 h at a concentration of 10% and a pressure of 0.1 MPa to obtain a carbonized cementitious product. The mechanical properties of the carbonized cementitious product were tested in accordance with GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", and the carbonization degree of the product was evaluated by the loss on ignition calcium carbonate method.

[0079] It is known from the test that the compressive strength of the carbonized cementitious material carbonized product of this comparative example (after carbonization for 24 hours) is 57.8MPa, and the degree of carbonization is 34.7%. It is known from the test that the compressive strength of the product increases with the increase of the insulation temperature, and the compressive strength can reach 82.2MPa when the insulation temperature is 1600℃. The degree of carbonization of the product shows an upward trend with the increase of the calcium-silicon molar ratio and the increase of the amount of lignin-based carbon fiber precursor added, and the highest degree of carbonization can reach 42.7%. In addition, according to the analysis of experimental test data, the increase of the calcium-silicon molar ratio and the increase of the content of lignin-based carbon fiber in the product have an improving effect on the performance of the product, and they cooperate with each other within a certain range to jointly improve the compressive strength of the product. However, when a certain proportion is exceeded, the two will hinder each other, which is not conducive to the improvement of the compressive strength of the product. This may be because the lignin-based carbon fibers are in-situ grown on the surface of the carbonized cementitious material, which significantly improves the bonding strength between the lignin-based carbon fibers and the carbonized cementitious material matrix and improves the interface transition zone; the steric hindrance effect of the lignin-based carbon fibers themselves is utilized to improve their dispersibility during the preparation and use process, fully exert the role of the lignin-based carbon fibers and the carbonized cementitious material and fill the original gaps in the carbonized cementitious material, so that the carbonized cementitious material is tightly combined. Within a certain range, the two work together to further improve the density of the carbonized cementitious material and effectively improve the comprehensive performance of the carbonized cementitious material.

[0080] The products of Examples 1 to 5 were tested for flexural strength, and the results are shown in Table 1.

[0081] Table 1 Flexural strength test results of products

[0082] Comparison Flexural strength(MPa) Example 1 5.2 Example 2 5.7 Example 3 5.3 Example 4 5.5 Example 5 5.8 Comparative Example 1 4.9

[0083] As can be seen from Table 1, the initial flexural strength of the product is improved after adding lignin-based carbon fiber, and the maximum is 5.8MPa when the mass ratio of lignin-based carbon fiber precursor to calcium silicon mixture is 0.1:1. The main reason may be that when the amount of lignin-based carbon fiber precursor added is small, it is limited by the loose connection area between the initial carbon fiber and the matrix. At this time, if subjected to compressive stress, the carbon fiber can only partially absorb internal micro-stress and hinder the expansion of micro-cracks, and because the connection with the matrix is ​​not strong, it may become a defect inside the sample to a certain extent. If the carbon fiber load limit is reached, the carbon fiber may suffer performance loss. With the increase of the amount of carbon fiber precursor added, the entanglement phenomenon of the carbon fiber itself is more obvious, which highlights the role of carbon fiber to a certain extent, and further improves the overall flexural strength of the product; the flexural strength of the product increases with the increase of the insulation temperature, and the flexural strength can reach 5.8MPa when the insulation temperature is 1600℃. In addition, according to the analysis of experimental test data, the increase of the calcium-silicon molar ratio and the content of lignin-based carbon fiber precursor in the product has a certain improvement effect on the performance of the product, and cooperates with each other within a certain range to jointly improve the flexural strength of the product. However, when it exceeds a certain ratio, the two restrict each other, which is not conducive to the improvement of the flexural strength of the product. This may be due to the fact that the lignin-based carbon fiber grows in situ on the surface of the carbonized cementitious material, which greatly improves the bonding strength between the lignin-based carbon fiber and the carbonized cementitious material matrix, and improves the interface transition zone; through the steric hindrance effect of the lignin-based carbon fiber itself, its dispersibility in the preparation and use process is improved, so that the carbonized cementitious material is tightly combined inside, and the comprehensive performance of the carbonized cementitious material is effectively improved.

[0084] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a carbonized gelled material, characterized in that: The following steps are involved: a) homogenizing a calcium raw material and a silicon raw material to obtain a calcium-silicon mixture; preparing lignin-based carbon fiber precursor by electrostatic spinning; the usage ratio of the calcium raw material to the silicon raw material is the molar ratio of calcium oxide in the calcium raw material to silicon dioxide in the silicon raw material (2-3):1; the lignin is selected from one or more of alkali lignin, organic solvent lignin and enzymatic lignin; the fiber diameter of the lignin-based carbon fiber precursor is 100nm-200nm, and the aspect ratio is 100-200; the electrostatic spinning preparation method of the lignin-based carbon fiber precursor is: lignin and polyacrylonitrile are uniformly mixed in a ratio of 1-7:99-93 to form a mixture A, and the mixture A and the solvent are mixed in a mass concentration ratio of 8-13:100 to prepare a lignin-based carbon fiber precursor spinning solution, and the solvent includes one or more of dimethyl sulfoxide, NN dimethylformamide, and NN dimethylacetamide; and then preparing the lignin-based carbon fiber precursor by electrostatic spinning; The parameters of the electrospinning process are as follows: the positive voltage of the high-voltage electric field is +10~20 kV, the negative voltage is -2~5 kV, the injection flow rate is 0.1~1.5 mL / h, the distance between the needle and the roller surface is 10~15 cm; the ambient temperature is 20~45℃, and the humidity is 35~50%; b) The calcium-silicon mixture and the lignin-based carbon fiber precursor are mixed and then pretreated and high-temperature treated in sequence, and then cooled to obtain a carbonized gelled material; the mass ratio of the calcium-silicon mixture and the lignin-based carbon fiber precursor is (0.01-0.1):1; the pretreatment method is preheating; the preheating temperature is 150°C-400°C, and the time is 2h-6h; the high-temperature treatment process is carried out under the protection of inert gas; the heating rate of the high-temperature treatment is 5°C / min-15°C / min, the temperature is 1050°C-1650°C, and the insulation time is 3h-9h.

2. The preparation method according to claim 1, characterized in that: The calcium raw material in step a) is selected from one or more of limestone, shell and steel slag; The siliceous raw material is selected from one or more of sandstone, coal slag and fly ash.

3. The preparation method according to claim 1, characterized in that: The homogenization treatment in step a) is carried out in one or more of a mixer and a ball mill.

4. A carbonized gelled material, characterized in that: The preparation method is described in any one of claims 1 to 3.

5. A carbonized gelled material product, characterized in that: The carbonized gelled material is prepared by carbonization curing; the carbonized gelled material is the carbonized gelled material according to claim 4.

6. The carbonized gelled material product according to claim 5, characterized in that: The carbonization curing time is 48h~86h, the concentration is 10%~100%, and the pressure is 0.1MPa~0.6MPa.

Citation Information

Patent Citations

  • Preparation method of gamma-C2S-based cementing material

    CN111393050A

  • Grinding-free carbonized hardened cement clinker and preparation method thereof

    CN111393051A

  • Preparation method of self-activated lignin-based micro-nano active carbon fibers with controllable pore diameters

    CN112760751A

  • Preparation of polyacrylonitrile / lignin carbon nanofiber electrode for sodium ion battery

    CN104269526A

  • Alkali lignin-based electrostatic spinning carbon fiber and preparation method and application thereof

    CN105862173A